The Arab Spring effect on Turkey's role, decision-making and foreign policy - Elhusseini, Fadi (Cambridge Scholars Publishing, 2018)
"This book analyses Turkey's role in the Arab world and investigates the effects of the Arab Spring on Turkish foreign policy, decision-making and its role. Particular attention is focused on widespread terms such as strategic depth, neo-Ottomans and the Turkish Model. It also provides incisive discussions of the key tenets of the Turkish official responses to Arab revolts and narrates the advantages and challenges that come to forge any potential regional role for Turkey."--